2021
DOI: 10.1002/bies.202100185
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the explanatory gaps: What can we learn from a biological agency perspective?

Abstract: We begin this article by delineating the explanatory gaps left by prevailing gene‐focused approaches in our understanding of phenotype determination, inheritance, and the origin of novel traits. We aim not to diminish the value of these approaches but to highlight where their implementation, despite best efforts, has encountered persistent limitations. We then discuss how each of these explanatory gaps can be addressed by expanding research foci to take into account biological agency—the capacity of living sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 152 publications
(161 reference statements)
1
72
0
Order By: Relevance
“…Agents of highly diverse implementation model their environments and themselves in accordance with an active inference framework, which drives the way they navigate information spaces. While dynamical systems theory describes how a system can go through a defined space, multi-scale agency models explain the shape of the space relative to specific observers and agents [ 247 ].…”
Section: Discussionmentioning
confidence: 99%
“…Agents of highly diverse implementation model their environments and themselves in accordance with an active inference framework, which drives the way they navigate information spaces. While dynamical systems theory describes how a system can go through a defined space, multi-scale agency models explain the shape of the space relative to specific observers and agents [ 247 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research in developmental biology has revealed that GP relationships tend to be complex (e.g., non-linear, non-additive, discontinuous) [3,28,29] , which explains why statistical approaches often have low predictive power. [30,31] The complexity of GP relationships arises from the reciprocal interactions between genes, between cells, and between genes and cells, that occur throughout development. [32] Understanding how GP relationships evolve, and how they influence future evolution, requires attention to these networks of interactions.…”
Section: The Genotype-phenotype Mapmentioning
confidence: 99%
“…331–333; our translation). In this perspective, development is “a highly constructive process, where a given aspect of phenotype formation builds upon a pre-existing phenotype created during previous stages of development” [ 26 ] (p. 7); see also [ 27 , 28 , 29 , 30 ]. In other terms, development goes on, so far as each phase is compatible with the preceding one, whereas the adultocentric view of development requires that each phase is compatible with the following.…”
Section: Developmental Patterns Vs Processesmentioning
confidence: 99%